Desktop audio technology digital audio and MIDI principles - Rumsey, Francis (Music technology series, 2004)
In this thorough introduction to the technology behind audio workstations, Dr Francis Rumsey explains not only how digital audio works but also how to make best use of its capabilities. A combined revision of his two successful titles, MIDI Systems and Control and The Audio Workstation Handbook, this new book covers recent developments such as surround sound formats, direct stream digital, new audio project formats, new interfaces and alternatives to MIDI. Desktop Audio Technology begins by setting out principles of digital audio and how these are applied in reco.